Development of a Cytotoxic T-Cell Assay in Rabbits to Evaluate Early Immune Response to Human T-Lymphotropic Virus Type 1 Infection - Haynes, Rashade A.H. (Mary Ann Liebert, Inc., 2009)
Human T-lymphotropic virus type 1 (HTLV-1) infection causes adult T-cell lymphoma/leukemia (ATL) following a prolonged clinical incubation period, despite a robust adaptive immune response against the virus. Early immune responses that allow establishment of the infection are difficult to study without effective animal models. We have developed a cytotoxic T-lymphocyte (CTL) assay to monitor the early events of HTLV-1 infection in rabbits. Rabbit skin fibroblast cell lines were established by transformation with a plasmid expressing simian virus 40 (SV40) large T antigen and used as autochthonous targets (derived from same individual animal) to measure CTL activity against HTLV-1 infection in rabbits. Recombinant vaccinia virus (rVV) constructs expressing either HTLV-1 envelope surface unit (SU) glycoprotein 46 or Tax proteins were used to infect fibroblast targets in a (51)Cr-release CTL assay. Rabbits inoculated with Jurkat T cells or ACH.2 cells (expressing ACH HTLV-1 molecule clone) were monitored at 0, 2, 4, 6, 8, 13, 21, and 34 wk post-infection. ACH.2-inoculated rabbits were monitored serologically and for viral infected cells following ex vivo culture. Proviral load analysis indicated that rabbits with higher proviral loads had significant CTL activity against HTLV-1 SU as early as 2 wk post-infection, while both low- and high-proviral-load groups had minimal Tax-specific CTL activity throughout the study. This first development of a stringent assay to measure HTLV-1 SU and Tax-specific CTL assay in the rabbit model will enhance immunopathogenesis studies of HTLV-1 infection. Our data suggest that during the early weeks following infection, HTLV-1-specific CTL responses are primarily targeted against Env-SU.